The Influence of Price, Promotion and Service on Purchasing Decisions (Loans) at Cooperatives Savings and Loan Cooperativetriaji Mandiri City Kediri - Yuni Eka Safitri; Eka Askafi; Deby Santyo Rusandy (International Journal of Economics Development Research (IJEDR), 2023)
The development of the Cooperative economy in Indonesia was increasingly advanced in various institutions, namely bank and non-bank institutions. Borrowing is a financial institution that offers services where savings and loan cooperatives must carry out promotional strategies on the products they offer. Tri Aji Mandiri Savings and Loan Cooperative was one of the individual/private savings and loan cooperatives whose activities offer services. Triaji Mandiri Cooperative, which was founded on 23 March 2010. This study aims to determine the effect of price, the effect of promotion, and the effect of service services on purchasing decisions at KSP Triaji Mandiri Kediri City. The research approach used was quantitative. Based on the results of the analysis and research that has been done, promotion has a partial effect on purchasing decisions (loans), which means that promotion has a significant effect on purchasing decisions (loans) for KSP Tri Aji Mandiri savings and loan cooperatives. Promotional activities in cooperatives are the most critical part because promotion is a process that can build relationships with cooperative members and foster value for members.